Crowdfunding as an Alternative Mode of Financing for Micro and Small Enterprises: A Proposed Qard-al-Hasan Contract - Abdulmajeed Muhammad Raji Aderemi; Muhammad Shahrul Ifwat Ishak (International Journal of Islamic Economics and Finance (IJIEF), 2020)
The global financial crisis that occurred in 2008, coupled with the evolution and globalization of social media and technology has made the evolvement of crowdfunding easy to use as a means of financing. However, the concept of crowdfunding is correlated with spiritual and religious responsibility which can increase the economic growth of Micro and Small Enterprises. In light of this, this paper aims to investigate the capacity of crowdfunding and proposes a crowdfunding model that adheres to the principle of Shari’ah by adopting a legitimate contract known as Qard-al-Hasan. In this regard, the study adopts qualitative research using secondary data with descriptive, and inductive approaches in the analysis. The result shows that Qard-al-Hasan based crowdfunding is great for pioneering business people to get access to financing their small and micro enterprises in compliance with Shariah. However, the findings of this paper will provide a new mechanism for financing micro and small enterprises in line with Shariah.